Mechanisms of tool wear in cubic boron nitride (CBN) during face milling of high hardness steels - V.O. Zaloga (Технічна інженерія)
The article is dedicated to the issues of tool wear with CBN in face milling of high hardness steels. In particular, the analytical study is aimed at identifying and classifying different types of wear that affect the efficiency and durability of the tools. The results of various researchersʼ experiments include the analysis of thermal wear caused by high temperatures generated in the cutting zone; abrasive wear caused by hard metal particles; and adhesive wear arising from the interaction of tool and workpiece materials. Experimental data shows that machining high hardness steels using CBN tools can ensure high quality of the machined surface, provided the correct cutting parameters selection. It has been determined that reducing the cutting speed and increasing the feed rate can significantly affect the reduction of tool wear. The article provides recommendations for optimizing machining parameters to achieve maximum efficiency. In particular, it proposes the use of multi-stage cutting strategies to reduce thermal and mechanical loads on the tool. Additionally, prospects for further research aimed at improving the face milling technology with the use of CBN tools are discussed, which can significantly increase the productivity and economic efficiency of manufacturing processes. The use of CBN tools is an effective solution for face milling of high hardness steels, but to achieve optimal results, it is necessary to consider the mechanisms of their wear and properly select cutting parameters.